2019
DOI: 10.3390/ma13010149
|View full text |Cite
|
Sign up to set email alerts
|

Surface Enhanced CdSe/ZnS QD/SiNP Electrochemical Immunosensor for the Detection of Mycobacterium Tuberculosis by Combination of CFP10-ESAT6 for Better Diagnostic Specificity

Abstract: In this study, an electrochemical immunosensor was introduced for the detection of tuberculosis (TB) via utilization of a modified electrode containing a quantum dot (CdSe/ZnS QD) and functionalized silica nanoparticles (SiNPs) on screen-printed carbon electrode (SPCE) CdSe/ZnS QD/SiNPs/SPCE, by employing indirect enzyme-linked immunosorbent assay (ELISA). Here, the fabricated electrode was linked to the biocatalytic action of enzyme catalase through antigen–antibody binding for the detection of the antigen (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…The results also show that the electroactive surface area of SPCE/MPA-Fe 3 O 4 /NCC/CTAB was increased by approximately 54.5% compared to the bare SPCE. This increment shows the ability of the developed electrochemical for providing a wide area platform [32] for DNA immobilization; thus, it can influence the sensitivity of detection [18,38]. Furthermore, the linearity of the plots has suggested that the electron transfer occurred was due to the diffusion-controlled electron transfer process [27,39].…”
Section: Electrochemical Characterizationmentioning
confidence: 88%
“…The results also show that the electroactive surface area of SPCE/MPA-Fe 3 O 4 /NCC/CTAB was increased by approximately 54.5% compared to the bare SPCE. This increment shows the ability of the developed electrochemical for providing a wide area platform [32] for DNA immobilization; thus, it can influence the sensitivity of detection [18,38]. Furthermore, the linearity of the plots has suggested that the electron transfer occurred was due to the diffusion-controlled electron transfer process [27,39].…”
Section: Electrochemical Characterizationmentioning
confidence: 88%
“…Bakhori et al, for the first time, developed an electrochemical immunosensor based on CdSE/ZnS quantum dots (QD) and silica nanoparticles (SiNPS) for Mycobacterium tuberculosis detection [ 41 ]. Screen-printed carbon electrodes were modified with CdSE/ZnS (QD) and SiNPs to amplify the detection signal as well as to increase the selectivity of the sensor.…”
Section: Pathogen Detection With Electrochemical Biosensorsmentioning
confidence: 99%
“…Weiner Kaufmann, 2020Ag85A, PPE, and pfkB Multistage DNA vaccine, A39 Su et al, 2017Ag85C, MPT5, and HspX rBCG-CMX da Costa et al, 2017 Lipo-AE vaccine formulation with the PolyIC adjuvant Diogo et al, 2019 ESAT-6, CFP-10, TB10.3, AlaDH, Ag85B, PstS1, andHspX ELISPOT assay Chiappini et al, 2012 38kD, ESAT-6, and CFP-10 Multiple-antigen detection assay Dai et al, 2017 CFP-10 and ESAT-6 Electrochemical-based SPCE Bakhori et al, 2020 ESAT-6, 6-kDa early secretory antigenic target; CFP, culture filtrate protein; rBCG, recombinant bacille Calmette-Guérin; ELISPOT, enzyme-linked immunospot assay; CMX, Ag85C-MPT51-HspX fusion protein; SPCE, screen-printed carbon electrode. For further details on Mycobacterium tuberculosis (Mtb) proteins, see the database: http://www.tbdb.org and http://tuberculist.epfl.ch immune response to the Ag85B antigen, but a weak immune response to ESAT-6 (Diogo et al, 2019).…”
Section: Id93mentioning
confidence: 99%